PENINGKATAN KEMAMPUAN MENGENAL KONSEP ANGKA MELALUI PERMAINAN PAPAN SELUNCUR KELERENG DI TAMAN KANAK-KANAK FADHILAH PADANG - Revina, Irna Wati (Universitas Negeri Padang, 2012)
Problems in this study the concept of low ability children in kindergarten Fadhilah Charity number 3 Padang, children are still many who are not familiar with the concept of a number, the child is not yet clear in showing the figures mentioned teachers, lack of playing time on the concept of numbers, MEDIA teachers used less variable. The goal is to improve children's ability to recognize the concept of numbers in kindergartens Fadhilah Amal 3 Padang. The results, in the first cycle increased rate of child knows the concept is still not good. Cycle II upgrades the child becomes familiar with the concept of rate increase. So that the average success rate of children is very satisfying.